(untitled) (PerCursos, 2024)
Black characters and writers have been marked by absences and stereotypes within the nacional literary sistem. Conceção Evaristo has, over decades as a blck writer, confronted these markings. The slavery proposed by Evaristo for her practice as a write is the narrative strategy for confronting the canon, as it reveals processes of violence and silencing of female characters. In this way, this article aims to analyse how this confrontation is established in the wor Insubmissas Lágrimas de mulheres (2011). How the narrator interconnects the narratives and characters based on their reports of violence and how they subverted such violence to tell their experiences. It is intended, therefore, from the perspective of Cândido (2011) regarding literature as a human right, to establish a dialogue with Evaristo’s narrative, in order to point out how the author builds a web of resistance of black female characters by giving them voice and place in narratives. TO support this objective, this article is based on black feminist researchers, whose debates point to intersectionality, such as Gonzalez (1984), Akotirene (2018), Collins (2016), Crenshaw (2002), from which they if the bibliographic review. With this reading of the work , the intentionality of writing remains demonstrated, as a narrative strategy to give voice and visibility to female characters traditionally silenced and stereotyped by the canon.